Fungal contamination in swine: a potential occupational health threat - Viegas, C. (2014)
Poor air quality in a pig-confinement building may potentially place farmers at higher health risk than other workers for exposure to airborne pollutants that may reach infectious levels. The aim of this study was to assess worker exposure to fungi in indoor environments in Portuguese swine buildings. Air samples from 7 swine farms were collected at a flow rate of 140 L/min, at 1 m height, onto malt extract agar supplemented with chloramphenicol (MEA). Surfaces samples of the same indoor sites were obtained by swabbing the surfaces. Samples from the floor covering were also collected from four of seven swine farms. All collected samples were incubated at 27◦C for 5–7 days. After lab processing and incubation of obtained samples, quantitative colony-forming units (CFU)/m3, CFU/cm2, and CFU/g and qualitative results were determined with identification of isolated fungal species. Aspergillus versicolor was the most frequent species found in air (21%), followed by Scopulariopsis brevicaulis (17%) and Penicillium sp. (14%). Aspergillus versicolor was also the most frequent species noted on surfaces (26.6%), followed by Cladosporium sp. (22.4%) and Scopulariopsis brevicaulis (17.5%). Chrysosporium was the most frequently found genera in the new floor covering (38.5%), while Mucor was the most prevalent genera (25.1%) in used floor covering. Our findings corroborate a potential occupational health threat due to fungi exposure and suggest the need for a preventive strategy.